Projected changes in solar UV radiation in the arctic and sub-arctic oceans: Effects from changes in reflectivity, ice transmittance, clouds, and ozone - Fountoulakis, Ilias; Bais, Alkiviadis F.; Tourpali, Kleareti D.; Fragkos, Konstantinos; Misios, S (My University, 2014)
Ultraviolet-B (UV-B), UV-A, and erythemal solar irradiance over ocean-covered areas north of 55°N are simulated for the past (1950–1960), present (2005–2015), and future (2090–2100) using a radiative transfer model. The simulations focus mainly on the effects of changes in ocean surface reflectivity, cloudiness, and stratospheric ozone. Based on projected changes in sea ice cover and thickness, changes in irradiance transmitted into the ocean are also derived. The input parameters of the radiative transfer model were obtained from four Coupled Model Intercomparison Project phase 5 Earth System Models driven by the emission scenarios Representative Concentration Pathway (RCP) 4.5 and RCP 8.5. Over a large fraction of the area under study, the overall effect from the projected changes in the factors considered is a reduction in the ultraviolet solar irradiance by the end of the 21st century relative to the levels in the 1950s. Increases were projected only for all skies during August for locations below 65°N due to the projected decrease in cloudiness. The reduction in clear-sky UV-A irradiance (on average 4–7% depending on scenario and season) is entirely driven by the reduction in surface reflectivity, while the projected ozone recovery is responsible for a great portion of the reduction in clear-sky UV-B irradiance (10–18% on average). Under all skies, the changes in the monthly mean noontime erythemal irradiance range from +15% to 38%, depending on the location and season. Compared to the 1950s, up to 10 times higher levels of UV-B irradiance are projected to enter large parts of the Arctic Ocean by 2100, mainly because of the partial disappearance of sea ice.
Keywords: Arctic Ocean; cloud; ozone; reflectivity; solar radiation; transmittance; ultraviolet radiation